A literary history of the Low Countries - Hermans, Theo (Camden House, 2009)
What was the written culture behind visual artists like Vermeer, Rembrandt, and Rubens? What made the historical novel in nineteenth-century Flanders so different from its counterpart in Holland? What was the literary impact of the huge colonial empires run by the Netherlands and Belgium? What role did Latin, French, and Frisian play in the literary culture of the Low Countries through the ages? Why is experimental writing so prevalent in modern Dutch literature? What has made Cees Nooteboom an internationally acclaimed author? And how does Flemish relate to Dutch anyway? This first liter.